Platinum-based chemotherapy induces methylation changes in blood DNA associated with overall survival in ovarian cancer patients - Flanagan,JM; Wilson,A; Koo,C; Masrour,N; Gallon,J; Loomis,E; Flower,K; Wilhelm-Benartzi,C; Hergovich,A; Cunnea,P; Gabra,H; Braicu,EI; et al. (Clinical Cancer Research, 2017)
PURPOSE: DNA damage repair can lead to epigenetic changes. DNA mismatch repair proteins bind to platinum DNA adducts and at sites of DNA damage can recruit the DNA methylating enzyme DNMT1, resulting in aberrant methylation. We hypothesised that DNA damage repair during platinum-based chemotherapy may cause aberrant DNA methylation in normal tissues of patients such as blood. EXPERIMENTAL DESIGN: We used Illumina 450k methylation arrays and bisulphite pyrosequencing to investigate methylation at presentation and relapse in blood DNA from ovarian cancer patients enrolled in the SCOTROC1 trial (n=247) and in a cohort of ovarian tumour DNA samples collected at first relapse (n=46). We used an ovarian cancer cell line model to investigate the role of the DNA mismatch repair gene MLH1 in platinum induced methylation changes. RESULTS: Specific CpG methylation changes in blood at relapse are observed following platinum-based chemotherapy and are associated with patient survival, independent of other clinical factors (HR=3.7; 95%CI 1.8-7.6, p=2.8x10-4). Similar changes occur in ovarian tumours at relapse, also associate with patient survival (HR=2.6; 95%CI 1.0-6.8, p=0.048). Using an ovarian cancer cell line model, we demonstrate that functional mismatch repair (MMR) increases the frequency of platinum-induced methylation. CONCLUSION: DNA methylation in blood at relapse following chemotherapy, and not at presentation, is informative about ovarian cancer patient survival. Functional DNA mismatch repair increases the frequency of DNA methylation changes induced by platinum. DNA methylation in blood following chemotherapy could provide a non-invasive means of monitoring patients' epigenetic responses to treatment without requiring a tumour biopsy.